Wuzhi capsule regulates chloroacetaldehyde pharmacokinetics behaviour and alleviates high‐dose cyclophosphamide‐induced nephrotoxicity and neurotoxicity in rats. Issue 2 (25th March 2019) - Chen, Li; Xiong, Xiaojuan; Hou, Xingyun; Wei, Hua; Zhai, Jianxiu; Xia, Tianyi; Gong, Xiaobin; Gao, Shouhong; Feng, Ge; Tao, Xia; Zhang, Feng; Chen, Wansheng
Abstract: High‐dose cyclophosphamide (HD‐CTX) treatment often leads to severe nephrotoxicity and neurotoxicity, which are mainly caused by one of its metabolites, chloroacetaldehyde (CAA). However, there are no effective antidotes to prevent these side effects. The objective of this study was to evaluate the effect of Wuzhi Capsule (WZC) on the pharmacokinetics of CTX and its metabolites in rats, and the attenuation of CAA induced kidney and brain injuries, which was produced at equimolar with 2‐dechloroethylcyclophosphamide. Rats were treated with single‐ or multiple‐dose of WZC when giving HD‐CTX, and the plasma concentration of CTX and its metabolites were quantitated by UHPLC‐MS/MS Single‐dose, not multiple‐dose of WZC co‐administration (300 mg/kg) significantly reduced C max and AUC0→24 h of DC‐CTX by 33.10% and 35.51%, respectively. Biochemical assay suggested oxidative stress was involved in kidney and brain injuries by HD‐CTX, which were attenuated by single‐dose WZC (300 mg/kg) pre‐treatment, with increased glutathione, glutathione peroxidase and superoxide dismutase contents/or activities in both tissues and plasma ( P  < 0.05). Meanwhile, WZC pre‐treatment could also significantly decrease the plasma levels of creatinine, blood urea nitrogen and malondialdehyde ( P  < 0.05). Additionally, WZC treatment improved the morphology and pathology condition of the kidneys and brains in rats. In conclusion, single‐dose WZC co‐administration decreased CAA production and exerted protective effect on CTX‐induced oxidative stress in kidney and brain, whereas repetitive WZC co‐administration with CTX was probably not recommended.